Automated design of scaffold-free DNA wireframe nanostructures - Wen Wang; Abdulmelik Mohammed; Rong Chen; Antti Elonen; Silian Chen; Mengfan Tian; Junhao Yang; Ye Xiang; Pekka Orponen; Bryan Wei (Nature Communications)
Abstract Computer-aided design has become common practice in DNA nanotechnology, and many programs are available that make the sophisticated design processes accessible to both the core research community and curious scientists in other fields. However, most of the design tools are committed to the scaffolded DNA origami method. Here we present an automated design pipeline for creating DNA wireframe nanostructures based on a scaffold-free molecular self-assembly approach. Unlike in the DNA origami method, scaffold-free designs are not built around a global backbone strand but are constituted entirely of short, locally intertwined oligonucleotides. This overcomes many limitations inherent in scaffolded nanostructure designs, most notably the size constraints imposed by the length of available scaffold strands, and the topological and algorithmic challenges of finding feasible scaffold-strand routings. In practice, this leads to simpler design flows and opens up new design possibilities. To demonstrate the flexibility and capability of our approach, we generate a variety of complex DNA wireframe designs automatically from 2D and 3D mesh models and successfully realise the respective molecular nanostructures experimentally.